2014
DOI: 10.1007/s11999-014-3733-4
|View full text |Cite
|
Sign up to set email alerts
|

What are the Patterns of Prophylactic Postoperative Oral Antibiotic Use After Foot and Ankle Surgery?

Abstract: Background The CDC estimates 23% of healthcareassociated infections to be surgical site infections, with alarming prevalence of antibiotic-resistant organisms. While there is consensus regarding preoperative prophylaxis, orthopaedic surgeons' use of prophylactic postoperative oral antibiotics is less defined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 51 publications
1
24
2
Order By: Relevance
“…Our findings are supported by several recent studies exploring current antimicrobial use practices following minor surgeries and procedures. A recent study used a cross-sectional questionnaire to measure current prolonged prophylaxis practices in outpatient foot surgeries and found that 75% of providers administer systemic oral post-procedure prophylactic antimicrobials, most commonly cephalexin for five to seven days [11]. Recent work on outpatient urology found that rates of prolonged prophylaxis are approximately 22% among community-based urologists – very similar to what we found in this VA population [12].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Our findings are supported by several recent studies exploring current antimicrobial use practices following minor surgeries and procedures. A recent study used a cross-sectional questionnaire to measure current prolonged prophylaxis practices in outpatient foot surgeries and found that 75% of providers administer systemic oral post-procedure prophylactic antimicrobials, most commonly cephalexin for five to seven days [11]. Recent work on outpatient urology found that rates of prolonged prophylaxis are approximately 22% among community-based urologists – very similar to what we found in this VA population [12].…”
Section: Discussionsupporting
confidence: 75%
“…Notably, the scope of this highly effective metric was limited only to a specific subset of major inpatient surgical procedures; outpatient procedures and some surgical subspecialties, including ENT and urology, were not included. In this large, multi-center, national VA cohort, we determined that implementation of early discontinuation of post-operative antimicrobial prophylaxis was strongly influenced by both surgical subspecialty and facility type; procedures performed within a large, complex hospital system were less likely to receive inappropriate prolonged post-procedural antimicrobial prophylaxis than the same procedures performed in ASCs and low-complexity hospital settings; this is supported by other recent work demonstrating high rates of inappropriate prolonged post-operative antimicrobial use in other outpatient and community settings [11, 12]. There was also a strong influence of surgical subspecialty type on the practice; prolonged prophylaxis was uncommon following orthopedic and general surgeries, which had procedures covered under the inpatient SCIP INF-3, but was frequent following ENT and urology procedures—which did not.…”
Section: Discussionmentioning
confidence: 80%
“…They underlined the necessity of using a suitable cost-effective oral antibiotic that also overcomes resistance mechanism of pathogens. [23] In the present study, it was observed that oral antibiotherapy was not preferred for pre-and postoperative periods in either hospital, which does not comply with literature data.…”
Section: Discussioncontrasting
confidence: 77%
“…In human medicine, postoperative oral antibiotics are common and the most commonly prescribed antibiotic is cephalexin . Despite their common use, several studies have reported no benefits to postoperative prophylactic antibiotics on the occurrence of SSI in clean orthopedic procedures .…”
Section: Discussionmentioning
confidence: 99%